2020
DOI: 10.3390/educsci10020037
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of an EFL Vocabulary Learning Mobile Application

Abstract: Mobile devices have penetrated all spheres of human activities, including education. Previous research has shown that smartphones are becoming widely used in learning as they can improve knowledge retention and increase student engagement. The purpose of this study was to discuss students’ perception of the use of a mobile application aimed at learning new English vocabulary and phrases and describe its strengths and weaknesses as perceived by the students. In total, 28 university students answered a pen and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 33 publications
(57 reference statements)
6
44
1
Order By: Relevance
“…The results presented by studies for the applications of pedagogy, reading, pronunciation, writing, listening, speaking, grammar outperformed the control group. It may be concluded that mobile applications for vocabulary learning have a positive impact on language learning in which pupils from the experimental group outperformed the control group except (Klimova & Polakova, 2020) (Ishaq et al, 2020b) where the students and teachers mentioned they are not satisfied with the design, content, assessment methods adopted in the applications besides pronunciation support and teachers' notifications were also missing. Gamified applications are proposed for vocabulary learning (Sandberg, Maris & Geus, 2011) (Sandberg, Maris & Hoogendoorn, 2014) (Wu, 2018) (Chen, Liu & Huang, 2019) (Fisser, Voogt & Bom, 2012), Spanish language learning (Holden & Sykes, 2011), Idioms (Amer, 2014), Vocabulary, Grammar, and Sentence Structure (Tsai et al, 2016), and Tenses, Words, Sentences (Önal, Çevik & Şenol, 2019).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results presented by studies for the applications of pedagogy, reading, pronunciation, writing, listening, speaking, grammar outperformed the control group. It may be concluded that mobile applications for vocabulary learning have a positive impact on language learning in which pupils from the experimental group outperformed the control group except (Klimova & Polakova, 2020) (Ishaq et al, 2020b) where the students and teachers mentioned they are not satisfied with the design, content, assessment methods adopted in the applications besides pronunciation support and teachers' notifications were also missing. Gamified applications are proposed for vocabulary learning (Sandberg, Maris & Geus, 2011) (Sandberg, Maris & Hoogendoorn, 2014) (Wu, 2018) (Chen, Liu & Huang, 2019) (Fisser, Voogt & Bom, 2012), Spanish language learning (Holden & Sykes, 2011), Idioms (Amer, 2014), Vocabulary, Grammar, and Sentence Structure (Tsai et al, 2016), and Tenses, Words, Sentences (Önal, Çevik & Şenol, 2019).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…This application helped pupils for the preparation of final exams by learning from anywhere at any time. To discuss students’ perception of using a mobile application, this was developed based on their needs to make EFL vocabulary teaching and learning useful ( Klimova & Polakova, 2020 ).…”
Section: Assessment and Discussion Of Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the methodological differences, the findings of all of the identified in two databases: Web of Science and Scopus studies showed that there was an improvement in reading comprehension after the treatment with mobile applications. In addition, a positive attitude was determined and enhanced learner motivation when using mobile apps was found in several studies [10]. Nevertheless, a great number of school teachers and university lectures are skeptical about introducing digital educational applications and they prefer not to use the educational means in their English classes.…”
Section: Discussionmentioning
confidence: 99%